2017
DOI: 10.1111/nph.14598
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungi and the enzymatic liberation of nitrogen from soil organic matter: why evolutionary history matters

Abstract: Contents Summary68I.Introduction68II.Have ECM fungi retained genes with lignocellulolytic potential from saprotrophic ancestors?69III.Are genes with saprotrophic function expressed by ECM fungi when in symbiosis?71IV.Do transcribed enzymes operate to obtain N from SOM?71V.Is the organic N derived from SOM transferred to the plant host?71VI.Concluding remarks72Acknowledgements72References72 Summary The view that ectomycorrhizal (ECM) fungi commonly participate in the enzymatic liberation of nitrogen (N) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 47 publications
6
112
0
Order By: Relevance
“…Is it possible, then, that some free‐living saprotrophic fungi have superior abilities in the mobilization and uptake of organic or occluded P compared with EMF? The lack of lignocellulolytic enzymes by some lineages of EMF, for example, may limit P liberation from organic substrates, as has been speculated for organic N acquisition (Pellitier & Zak, ). Likewise, Talbot et al .…”
Section: Discussionmentioning
confidence: 96%
“…Is it possible, then, that some free‐living saprotrophic fungi have superior abilities in the mobilization and uptake of organic or occluded P compared with EMF? The lack of lignocellulolytic enzymes by some lineages of EMF, for example, may limit P liberation from organic substrates, as has been speculated for organic N acquisition (Pellitier & Zak, ). Likewise, Talbot et al .…”
Section: Discussionmentioning
confidence: 96%
“…Being facultative saprotrophs, Mucoromycotina fungi (Field et al ., 2015b) may be able to gain both C and N from organic sources, in a similar manner to some ECMF (Smith & Read, ; but see Lindahl & Tunlid, ), and would be in a position to then transfer N to their plant partners whilst remaining less reliant on the hosts to meet their C requirements. It should be noted, however, that the notion that ECMF are able to enzymatically liberate N from soil organic matter and to then transfer N to host plants is far from settled (Pellitier & Zak, , and references therein). Recent studies have shown that ECM have a reduced complement of genes encoding plant cell wall‐degrading enzymes than their saprotrophic ancestors – although the occurrence of these genes varies considerably across ECMF lineages – and thus have limited capacity to decompose soil lignocellulose (Martin et al ., ; Kohler et al ., ).…”
Section: Mycorrhizal Unity In Host Plant Nutritionmentioning
confidence: 99%
“…Certain groups of EMF may have the capacity to liberate and assimilate mineral-bound forms of organic N; hydrophobic EMF may be better equipped in this regard due to their capacity to access more insoluble forms of N (Hobbie et al 2012;Chen et al 2016). Not all lineages of EMF are uniformly equipped to produce oxidative enzymes (Pellitier and Zak 2018) and other fungi, such as saprotrophic or ericoid mycorrhizal fungi, have an overall greater capacity to produce such enzymes (Bending and Read 1996;Wu 2011). More studies are needed to identify the fungal taxa that can produce the enzymes needed to mobilize N from MAOM.…”
Section: Strength Of Organo-mineral Associationsmentioning
confidence: 99%